LAWYERS IN COLOR AND GENDER: THE UNEQUAL IMPACTS OF COVID-19 ON THE PRACTICE OF LAWYERS IN THE STATE OF RIO DE JANEIRO - dos Santos, Eneida Maria; de Lacerda Carelli, Rodrigo; Matosinhos, Isabella (Revista de Estudos Empíricos em Direito, 2021)
The Covid-19 pandemic had important consequences in the practice of lawyers, but it also represented serious economic impacts for these professionals. The study was based on empirical research conducted with male and female lawyers in the state of Rio de Janeiro, Brazil. The results demonstrate that the impacts of the pandemic on work and on the economic condition of these professionals were greater for blacks and, in an intersectional analysis, for black women. The conclusion is that there is an unequal distribution of the effects of the pandemic in relation to these groups, which are socially and economically vulnerable. In order to interpret the data found, a literature review was conducted on racial, feminist and black feminism studies, which clarify the history of oppression of these groups and the socially constructed narratives that cause black men, black women and women to be discrimated against in the labor market in the 21st century. The study also brings a special look to black women, since they are in a more precarious situation by experiencing the abuses of racial and gender categories together. This point of view is elucidated from the theory of intersectionality.